Efficacy of emergency transarterial embolization in acute lower gastrointestinal bleeding: A single-center experience - C. Bua-Ngam (2018)
© 2017 Editions francaises de radiologie. Published by Elsevier Masson SAS. All rights reserved. Purpose: The purpose of this study was to assess the safety and efficacy of transcatheter arterial embolization (TAE) in the treatment of acute lower gastrointestinal bleeding (LGIB) and to determine the potential factors that influence treatment outcome. Material and methods: A total of 38 patients with acute LGIB who were treated by TAE were retrospectively included. There were 24 men and 14 women, with a mean age of 61 years (range: 9-84 years). Patient characteristics, laboratory findings, treatments, causes of bleeding, angiographic findings, and outcomes were reviewed. Results: Active contrast extravasation was observed in 26/38 patients (68.4%) and was the most frequent angiographic finding, followed by abnormal mucosal staining (8/38; 21.1%) and tumor staining (4/38; 10.5%). Technical success of TAE was obtained in 35/38 patients (92%) whereas technical failure was observed in 3/38 patients (8%). Clinical success rate following TAE was 63%. Bowel ischemia occurred in 5/38 patients (13%) following TAE; mild ischemia without sequelae was observed in 3 patients and severe ischemias with bowel perforation requiring surgery in 2 patients. No variables were identified as significant predictive factors of failed TAE. Conclusion: TAE is a safe and effective treatment to control massive acute LGIB, especially in the emergency setting with a clinical success rate of 63%.